Synthesis and Characterization of Mono Nuclear Complexes of Mn2+, Ni2+ and Cu2+ with Tetradentate N3O Schiff Base - MANJUNATHAN, S.; KRISHNAN, C.N. (Asian Journal of Chemistry, 2010)
An unsymmetrical Schiff base ambsalen, [1-(2-aminobenzylideneiminato)-2-(salicylaldiminato) ethane] derived by the condensation of ethylenediamine with equimolar amounts of o-aminobenzal-dehyde and salicylaldehyde was synthesized and was characterized. The copper(II), nickel(II) and manganese(II) complexes of the ligand ambsalen were also synthesized and characterized by elemental analysis, conductivity, 1H NMR, UV-Vis, IR, EPR spectral studies and cyclic voltammetry. The molar conductivity data of the mononuclear complexes showed them to be 1:1 electrolytes. The tetradentate nature of the ligand is concluded from the IR spectral studies. The electronic spectral data suggest planar geometry for all the complexes. The antibacterial activities of the ligand and their metal complexes have been screened in vitro for their antibacterial and antifungal activities.